Roles of microglia in the healthy brain - Tremblay, Marie-Ève (Henry Stewart Talks, 2022)
Introduction to microglia, Extreme dynamism in vivo, Interactions with synapses, Roles in the healthy brain, Fractalkine signaling, TAM receptors, Complement pathway, Microglial BDNF, CSF1R inhibition, TREM2, Microglial diversity, Microglia in disease, CX3CR1-GFP mice